Modernization of the poetic tradition in the Balkarian literature of the 1920s and 1930s (K.B. Mechiev, S.O. Shakhmurzaev) - Kazim K. Bauaev (Кавказология, 2025)
The work contains analytical information about the processes of aesthetic unification and national identity of the North Caucasian literatures of the early twentieth century. The focus is on reflections on the nature of the ideological factors that influenced the division of national literatures into "traditional" and "newly written" ones. Based on the poetic works of K. Mechiev and S. Shakhmurzaev, the problem of continuity and isolation of Balkarian literature, the processes of modernization of national author's poetry of the 1920s and 1930s are analyzed. It is shown that in the context of a sharp expansion of the thematic and problematic fields of young Soviet poetry, which was observed even during the tightening of the cultural policy of the state, the Balkan poets consciously and purposefully built in their works a new system of imaginative presentations based not only on traditional sensitive structures, but also – to a greater extent – on reflective schemes of denotative, generalized conceptual character. The author comes to the conclusion that the physical fullness of the images of Balkarian poetry, their materiality, emanating from the perceptual resources of the language itself, in the late 30s of the last century determines the parameters of poetic representations of most authors. It is inherent even to those of them whose individual style, pathos and conceptualism were completely determined by the standards of the ideological order and formed within the boundaries of the socialist abstract emblems.